Effect of uncertainty in sorbent characteristic on techno-economic feasibility of carbonate looping for decarbonisation of coal-fired power plant - Hanak, Dawid P. (Wiley, 2022)
Carbon capture, utilisation and storage (CCUS) technologies are forecasted to significantly contribute to the decarbonisation of the power sector. Chemical solvent scrubbing is now considered the most mature CCUS technology. Yet, its integration with fossil fuel power plants is forecasted to reduce the net efficiency of the entire process by at least 7% points, resulting in the avoided CO2 cost of 35 to 75 €/tCO2. Carbonate looping (CaL) has been demonstrated to be an emerging technology for decarbonisation of the power sector with lower efficiency (>5% points) and economic penalties (10-30 €/tCO2). The key challenge that may influence the viability of CaL is the decay in the sorbent CO2 uptake. Such a deterioration in sorbent performance is usually accounted for in the techno-economic assessments via semi-empirical correlations. Yet, such correlations include fitting parameters based on experimental data that is, in turn, associated with ±20% measurement error. This study employed a stochastic approach to quantify the impact of such uncertainty in the sorbent characteristics on the techno-economic performance of a 580 MWel coal-fired power plant with CaL retrofit. The stochastic assessment showed that the most likely figures for the efficiency penalty would fall between 7.7 and 8.7% points, with a median of 8.08% points. Such a figure was higher than the one determined using the deterministic approach (7.85% points). Moreover, the estimated CO2 avoided cost was between 29.74 and 46.50 €/tCO2, with a median of 35.94 €/tCO2. Such a figure was higher than that obtained in the deterministic assessment (32.40 €/tCO2). It implied that the economic assessment using the deterministic approach could underestimate the costs associated with the CaL retrofits. This study, therefore, revealed that the uncertainty in the sorbent characteristics would influence the techno-economic viability of the CaL retrofits.
Keywords: calcium looping; carbon capture; decarbonisation; stochastic modelling; techno-economic analysis